2023
DOI: 10.3390/molecules28020578
|View full text |Cite
|
Sign up to set email alerts
|

Obtaining 2,3-Dihydrobenzofuran and 3-Epilupeol from Ageratina pichinchensis (Kunth) R.King & Ho.Rob. Cell Cultures Grown in Shake Flasks under Photoperiod and Darkness, and Its Scale-Up to an Airlift Bioreactor for Enhanced Production

Abstract: Ageratina pichinchensis (Kunth) R.King & Ho.Rob. is a plant used in traditional Mexican medicine, and some biotechnological studies have shown that its calluses and cell suspension cultures can produce important anti-inflammatory compounds. In this study, we established a cell culture of A. pichinchensis in a 2 L airlift bioreactor and evaluated the production of the anti-inflammatory compounds 2,3-dihydrobenzofuran (1) and 3-epilupeol (2). The maximum biomass production (11.90 ± 2.48 g/L) was reached at 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…On the other hand, the compounds stigmasterol (5), stigmasterol glucoside (11), and β-sitosterol (6) are considered some of the predominant compounds in plants [50,51]. Their pharmacological studies have shown their antimicrobial, anti-inflammatory, antiosteoarthritic, anti-tumor, cytotoxic, anti-hypercholesterolemia, and antioxidant activities [52][53][54][55].…”
Section: Chemical Profile Of Ethyl Acetate Extract Of Callus Culturesmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, the compounds stigmasterol (5), stigmasterol glucoside (11), and β-sitosterol (6) are considered some of the predominant compounds in plants [50,51]. Their pharmacological studies have shown their antimicrobial, anti-inflammatory, antiosteoarthritic, anti-tumor, cytotoxic, anti-hypercholesterolemia, and antioxidant activities [52][53][54][55].…”
Section: Chemical Profile Of Ethyl Acetate Extract Of Callus Culturesmentioning
confidence: 99%
“…Moreover, compound (7) exhibits chirality, which complicates the development of synthesis routes to obtain it. On the other hand, our research group has reported the production of the compound through suspension cell cultures in flasks as well as in airlift reactors, significantly improving its production and possible scaling [10,11], which provides a viable and sustainable alternative to produce the compound.…”
Section: Cytotoxic Effect Of the Compound 23-dihydrobenzofuranmentioning
confidence: 99%
See 2 more Smart Citations